Roles of ATP-dependent N-acylhomoserine lactones (AHLs) and extracellular polymeric substances (EPSs) in aerobic granulation - Jiang, Bo (2013)
Aerobic granules which form through a cell-to-cell self-immobilization process have been intensively studied and developed for wastewater biotreatment. However, the microbiological origin of this phenomenon is still largely unknown. This study investigated the possible role of metabolic energy in the development of aerobic granules. Results showed that aerobic granulation was positively related to ATP-dependent N-acylhomoserine lactones (AHLs) and extracellular polymeric substances (EPSs) production. Inhibited ATP synthesis by a chemical uncoupler, 3,3′,4′,5-tetrachlorosalicylanilide, led to significant reduction of AHLs and EPSs production, which in turn prevented aerobic granulation. This study for the first time demonstrated the involvement of ATP-dependent AHLs in aerobic granulation.